The influence of information costs on the integration of financial markets: Northern Europe, 1350-1560 - Oliver Volckart (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2006)
In this paper, the influence of information costs on the integration of Northern European financial markets between ca. 1350 and 1560 is explored. The approach is based on splitting information costs into their constitutive components and on measuring one of these, i.e. the costs of transmitting information, which have particular importance for market integration. The analysis has two main results: First, under pre-industrial conditions, when transmitting information was extremely labour intensive and very little capital intensive, transmission costs can be largely identified with labour costs, and were subject to the same influences. Next, the integration of financial markets depended crucially on the level of transmission costs, high costs being strongly and significantly correlated with weak integration, while lower costs favoured convergence.
Keywords: E44; F31; F36; N24; 330; Financial markets; integration; information costs; economic history